1966
DOI: 10.3181/00379727-123-31391
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Excretion of Furosemide-S35 in Human Subjects

Abstract: 17time from pool acetate to expired C02 as 60 minutes which is slightly shorter than the half life from the carboxyl carbon of acetate to C02 obtained in this investigation of 76.5 minutes. This result following equilibration during an infusion period is probably a better figure than that obtained following a single injection. The longer half life (135 min) of conversion from the methyl carbon of acetate to pool C02 found when 2-C14 acetate was infused, emphasizes the difference in the pathway of oxidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1967
1967
1980
1980

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 1 publication
2
22
0
Order By: Relevance
“…The shortest T, aL in our study was twice as long as mean values reported for normal volunteers or patients with uremia (Andreasen & Mikkelson, 1977; Calesnick, Christensen & Richter, 1966;Rane, Villeneuve, Stone, Neis, Wilkinson & Branch, 1978).…”
Section: Discussionsupporting
confidence: 58%
“…The shortest T, aL in our study was twice as long as mean values reported for normal volunteers or patients with uremia (Andreasen & Mikkelson, 1977; Calesnick, Christensen & Richter, 1966;Rane, Villeneuve, Stone, Neis, Wilkinson & Branch, 1978).…”
Section: Discussionsupporting
confidence: 58%
“…1 , 19 This greater potency is not explained by differences in drug absorption as roughly the same proportions of equipotent oral doses of both drugs are excreted in the urine. 3 Bumetanide is rapidly absorbed from the gut as shown by the early peaks in serum concentration after oral administration and the similar magnitude of total natriuretic response after oral and intravenous administration of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy persons. -Calesnick et al (7) found that in two healthy volunteers given 35S-furosemide at the dosage of 50 mg the maximum plasma radioactivity levels were observed after 60 minutes. Kelly et al (16) observed no differences in drug absorption whether administered in the form of tablets or solution.…”
Section: Oral Administrationmentioning
confidence: 98%
“…Most pharmacokinetic data have been obtained using preparations labelled with radioactive sulfur (7,16,32,33) and carbon (20,22,26,27,28). The drug's concentration in biologic fluids can also be measured using Bratton and Marshall diazotization method.…”
mentioning
confidence: 99%